Can extranodal tumour deposits be diagnosed on MRI? Protocol for a multicentre clinical trial (the COMET trial) - Shahnawaz Rasheed; Amy C Lord; Brendan Moran; Muti Abulafi; Iris D Nagtegaal; Monica Terlizzo; Gina Brown (BMJ Open)
Introduction Tumour deposits (TDs) are a poor prognostic marker when seen on pathology, and are worse than lymph node metastases (LNMs). They are now being reported on MRI as discontinuous nodules of extramural venous invasion but this diagnosis has not been validated and it is unclear how it correlates with the diagnosis of TDs on pathology.Methods and analysis This is a prospective interventional clinical trial which aims to directly map the location of TDs on MRI and correlate what is seen on MRI with the pathology findings at each location. All patients with rectal cancer undergoing resectional surgery are eligible (including those undergoing preoperative therapy). The primary outcome is the prevalence of TDs seen on pathology. Secondary outcomes are to assess radiological and pathological interobserver agreement, assess the effect of TDs on prognosis and carry out exploratory work looking at differences between TDs and LNMs. The estimated sample size is 100 to detect a twofold increase in the pathological diagnosis of TD when MRI mapping is used.Ethics and dissemination Ethical approval has been granted from the South Central—Hampshire B Research and Ethics Committee (IRAS 217627). The study will be carried out under standard operative procedures within the Royal Marsden Hospital.Trial registration number NCT03303547.